2018
DOI: 10.3390/catal8050221
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reduction of Ketones and Aldehydes in Continuous-Flow Microreactor—Kinetic Studies

Abstract: Abstract:In this work, the kinetics of Meerwein-Ponndorf-Verley chemoselective reduction of carbonyl compounds was studied in monolithic continuous-flow microreactors. To the best of our knowledge, this is the first report on the MPV reaction kinetics performed in a flow process. The microreactors are a very attractive alternative to the batch reactors conventionally used in this process. The proposed micro-flow system for synthesis of unsaturated secondary alcohols proved to be very efficient and easily contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The recent study of the MPV reduction of a number of aldehydes and ketones, with 2-butanol in 0.14Zr-Pr-MMRs with the M1 structure, showed that its kinetics can be quantified by the first-order kinetics equation (Ciemięga et al, 2018;. First, preliminary experiments performed using reactors 10-80 mm of length (4.5 mm dia., velocities varying from 2 to 16 mm/min) clearly proved the lack of external mass transport limitation of reaction kinetics (Maresz et al, 2018). The temperature dependence of the reaction rate allowed for the estimation of the activation energy for the reduction of hexanone as equal to 52 kJ/mol and the frequency factor k 2.69 1/min.…”
Section: Monolithic Microchannel Reactors Functionalized With Transition Metalsmentioning
confidence: 88%
See 1 more Smart Citation
“…The recent study of the MPV reduction of a number of aldehydes and ketones, with 2-butanol in 0.14Zr-Pr-MMRs with the M1 structure, showed that its kinetics can be quantified by the first-order kinetics equation (Ciemięga et al, 2018;. First, preliminary experiments performed using reactors 10-80 mm of length (4.5 mm dia., velocities varying from 2 to 16 mm/min) clearly proved the lack of external mass transport limitation of reaction kinetics (Maresz et al, 2018). The temperature dependence of the reaction rate allowed for the estimation of the activation energy for the reduction of hexanone as equal to 52 kJ/mol and the frequency factor k 2.69 1/min.…”
Section: Monolithic Microchannel Reactors Functionalized With Transition Metalsmentioning
confidence: 88%
“…The performance of MMRs doped with various Lewis acid centers has been extensively studied in the chemoselective Meerwein-Ponndorf-Verley (MPV) reduction of carbonyl compounds-a widespread route for the synthesis of unsaturated secondary alcohols, and the results have been presented in a series of articles (Koreniuk et al, 2015a;Ciemięga et al, 2017b;Ciemięga et al, 2018;Maresz et al, 2018;. Preliminary studies showed that modification of silica monoliths (M1 structure) with zirconium (IV) propoxide (Zr-Pr-MMR) resulted in the formation of zirconium complexes with mixed propoxy/hydroxyl ligands bound to the silica surface, which were much more catalytically active than silica-supported zirconia (Zr-MMR) (Koreniuk et al, 2015a).…”
Section: Monolithic Microchannel Reactors Functionalized With Transition Metalsmentioning
confidence: 99%
“…3 The high-pressure involved in such a chemical process requires expensive equipment and an elaborate experimental set-up with associated safety risks. 4,5 The problems associated with these classical methods could be avoided in the Meerwein-Ponndorf-Verley (MPV) reduction.…”
Section: Introductionmentioning
confidence: 99%
“…All the prepared materials were successfully employed, under flow conditions, for the hydrogenation of methyl levulinate using 2-propanol as the hydrogen donor. Better performance was observed with catalysts possessing higher dispersion of ZrO 2 particles.Monolithic flow microreactors were employed for studying the kinetics of the Meerwein-Ponndorf-Verley reduction of carbonyl compounds [5]. Zirconium-functionalized silica monoliths constituted the core of the reactor and performed well in promoting the reduction of cyclohexanone and other ketones and aldehydes using 2-butanol as the hydrogen donor.…”
mentioning
confidence: 99%
“…Monolithic flow microreactors were employed for studying the kinetics of the Meerwein-Ponndorf-Verley reduction of carbonyl compounds [5]. Zirconium-functionalized silica monoliths constituted the core of the reactor and performed well in promoting the reduction of cyclohexanone and other ketones and aldehydes using 2-butanol as the hydrogen donor.…”
mentioning
confidence: 99%